Molecular modeling study of para amino benzoic acids recognition by β-cyclodextrin - Fatiha, Madi; Djameleddine, Khatmi; Leila, largate (Orbital: The Electronic Journal of Chemistry, 2008)
AM1 and PM3 methods were applied to investigate equilibrium geometries of inclusion complexes formed between ß-CD and neutral, anionic and cationic species of PABA (Para amino benzoic acid). ß-CD can bind to these three species (two possible orientations A or B) with negative binding energy, where the preference between A and B orientation of each PABA species is due to H-bond interaction. Finally, the HOMO and LUMO energies of each complex were calculated and compared.